Aksesibilitas Narapidana Penyandang Disabilitas (Studi Kasus di Rutan Kelas I Surakarta) - Irawan, Andrie; Widodo, Yohanes Yunianto (Sharia Journal and Education Center Publishing, 2024)
Abstract This study aims to find out how Accessibility for Prisoners with Disabilities in Class I State Prison Surakarta and the obstacles experienced. The research method used is an empirical method, with data collection techniques, namely interview studies and literature studies. The data is complemented by primary data from interview results, and secondary data from references such as applicable laws and regulations, with a descriptive qualitative analysis method. This research was conducted in a class I prison in Surakarta. The results of the research and analysis show that in order to create a welcoming and accessible environment for all individuals, especially people with disabilities, two main things are needed: accessibility that includes physical convenience and people's attitudes towards disabilities, and mobility that guarantees the ability of individuals to move independently. Legal protection as stipulated in Law Number 8 of 2016 and local policies such as Surakarta City Regional Regulation Number 9 of 2020 are the basis for ensuring that these rights are fulfilled, both in the context of the general public and in institutions such as the State Prison (Rutan), where a rehabilitative approach and disability-sensitive services are essential to ensure inclusion and fair treatment. However, the fulfillment of this right is often hampered by several factors. The absence of clear procedures in Law Number 22 of 2022 concerning Corrections regarding special services for people with disabilities is one of the main obstacles. In addition, the facilities and accessibility infrastructure in the prison that are still inadequate also affect the mobility and independence of inmates with disabilities. Lack of knowledge and understanding of disability among prison officers and inadequate regulations are also significant inhibiting factors. To improve this condition, joint efforts are needed between the Detention Center, the government, and community organizations to ensure the fulfillment of accessibility rights and fair treatment for inmates with disabilities, in accordance with the principles of justice and humanity in the correctional system. Keywords : Accessibility, Prisoners, Persons with Disabilities Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana Aksesibilitas Bagi Narapidana Penyandang Disabilitas Di Rumah Tahanan Negara Kelas I Surakarta serta hambatan yang dialami. Metode penelitian yang digunakan merupakan metode empiris, dengan teknik pengumpulan data yaitu studi wawancara dan studi kepustakaan. Data dilengkapi dengan data primer dari hasil wawancara, dan data sekunder dari referensi-referensi seperti peraturan perundang-undangan yang berlaku, dengan metode analisis kualitatif secara deskriptif. Penelitian ini dilakukan di Rutan kelas I Surakarta.Hasil penelitian dan analisis menunjukkan bahwa Untuk menciptakan lingkungan yang ramah dan mudah diakses bagi semua individu, terutama penyandang disabilitas, diperlukan dua hal utama: aksesibilitas yang mencakup kemudahan fisik dan sikap masyarakat terhadap disabilitas, serta mobilitas yang menjamin kemampuan individu untuk bergerak secara mandiri. Perlindungan hukum seperti yang diatur dalam Undang-Undang Nomor 8 Tahun 2016 dan kebijakan lokal seperti Peraturan Daerah Kota Surakarta Nomor 9 Tahun 2020 menjadi landasan untuk memastikan hak-hak ini terpenuhi, baik dalam konteks masyarakat umum maupun di institusi seperti Rumah Tahanan Negara (Rutan), di mana pendekatan rehabilitatif dan layanan yang sensitif terhadap disabilitas sangat penting untuk memastikan inklusi dan perlakuan yang adil.Namun, pemenuhan hak ini sering terhambat oleh beberapa faktor. Absennya prosedur yang jelas dalam Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan mengenai pelayanan khusus bagi disabilitas menjadi salah satu hambatan utama. Selain itu, sarana dan prasarana aksesibilitas di dalam Rutan yang masih kurang memadai juga mempengaruhi mobilitas dan kemandirian narapidana disabilitas. Kurangnya pengetahuan dan pemahaman tentang disabilitas di kalangan petugas Rutan serta regulasi yang belum memadai juga menjadi faktor penghambat yang signifikan. Untuk meningkatkan kondisi ini, perlu upaya bersama antara Rutan, pemerintah, dan organisasi masyarakat untuk memastikan pemenuhan hak-hak aksesibilitas dan penanganan yang adil bagi narapidana penyandang disabilitas, sesuai dengan prinsip keadilan dan kemanusiaan dalam sistem pemasyarakatan. Kata Kunci : Aksesibilitas, Narapidana, Penyandang Disabilitas